2009
DOI: 10.1111/j.1365-2966.2009.14272.x
|View full text |Cite
|
Sign up to set email alerts
|

A new determination of the orbit and masses of the Be binary system δ Scorpii

Abstract: The binary star δ Sco (HD143275) underwent remarkable brightening in the visible in 2000, and continues to be irregularly variable. The system was observed with the Sydney University Stellar Interferometer (SUSI) in 1999, 2000, 2001, 2006 and 2007. The 1999 observations were consistent with predictions based on the previously published orbital elements. The subsequent observations can only be explained by assuming that an optically bright emission region with an angular size of ≳2 ± 1 mas formed around the pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 36 publications
4
62
0
1
Order By: Relevance
“…It is interesting to speculate that the periastron passage in 2000 contributed to the observed brightening. The secondary companion has a very eccentric orbit with a period of about 11 yr (for recent calculations see Tango et al 2009;Tycner et al 2011;Meilland et al 2011) and the periastron passage of its companion in 2011 offered an opportunity to study this system. We collected V-and B-band photometry for the 2009, In this work we use our V and B photometry to probe the innermost regions of the disk of δ Sco in order to determine the mass-loss rate and investigate the variability of these outbursts for this system.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to speculate that the periastron passage in 2000 contributed to the observed brightening. The secondary companion has a very eccentric orbit with a period of about 11 yr (for recent calculations see Tango et al 2009;Tycner et al 2011;Meilland et al 2011) and the periastron passage of its companion in 2011 offered an opportunity to study this system. We collected V-and B-band photometry for the 2009, In this work we use our V and B photometry to probe the innermost regions of the disk of δ Sco in order to determine the mass-loss rate and investigate the variability of these outbursts for this system.…”
Section: Introductionmentioning
confidence: 99%
“…Observational data supporting the idea of mass-loss events associated with periastron passage exist for the highly eccentric (e ∼ 0.94) binary δ Sco (Bedding 1993;Miroshnichenko et al 2001;Tango et al 2009). And Millour et al (2009) suggested that the dusty circumbinary environment in HD 87643 might be associated with repeated close encounters in the long period and possible highly eccentric binary.…”
Section: Introductionmentioning
confidence: 79%
“…The uncertainty of the projected separation obtained is in the sub-milliarcseconds regime (Armstrong et al, 2004;Davis et al, 2005;Tango et al, 2009). …”
Section: Methodsmentioning
confidence: 98%
“…This means this indirect method is not suitable for narrow-angle astrometry for stars that have a wider projected separation. This is the main reason why most of the past experiments (Armstrong et al, 2004;Davis et al, 2005;Tango et al, 2009) using this method is limited to speckle binaries and relatively short baselines.…”
Section: Methodsmentioning
confidence: 99%